2021
DOI: 10.3389/fonc.2021.769385
|View full text |Cite
|
Sign up to set email alerts
|

HIF2 Regulates Intestinal Wnt5a Expression

Abstract: Radiation therapy for abdominal tumors is challenging because the small intestine is exquisitely radiosensitive. Unfortunately, there are no FDA-approved therapies to prevent or mitigate GI radiotoxicity. The EGLN protein family are oxygen sensors that regulate cell survival and metabolism through the degradation of hypoxia-inducible factors (HIFs). Our group has previously shown that stabilization of HIF2 through genetic deletion or pharmacologic inhibition of the EGLNs mitigates and protects against GI radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…WNT5A mediates the activation of Tregs and tumor-associated macrophages (TAM), which thereby induces immunosuppression during the progression of castration-resistant prostate cancer ( 44 ). WNT5A may be a potential target for the prevention of gastrointestinal radiotoxicity because its absence impairs the ability of individual intestinal stem cells (ISCs) to form crypt spheroids after irradiation, whereas the addition of WNT5A saves ISCs from radiation-induced cell death ( 45 ). Tumor angiogenesis is considered an important phenomenon in the progression of tumors and is associated with overexpression of Neuropilin1 (NRP1) receptors.…”
Section: Discussionmentioning
confidence: 99%
“…WNT5A mediates the activation of Tregs and tumor-associated macrophages (TAM), which thereby induces immunosuppression during the progression of castration-resistant prostate cancer ( 44 ). WNT5A may be a potential target for the prevention of gastrointestinal radiotoxicity because its absence impairs the ability of individual intestinal stem cells (ISCs) to form crypt spheroids after irradiation, whereas the addition of WNT5A saves ISCs from radiation-induced cell death ( 45 ). Tumor angiogenesis is considered an important phenomenon in the progression of tumors and is associated with overexpression of Neuropilin1 (NRP1) receptors.…”
Section: Discussionmentioning
confidence: 99%
“…HIF2α regulates β-catenin activity by direct and indirect mechanisms. HIF2α was shown to directly interact with β-catenin (117) or increase WNT5A expression (118) thereby enhancing β-catenin/TCF-driven transcriptional responses. However, HIF1α negatively regulated Wnt/β-catenin signaling (119).…”
Section: Hifs In Oncogenic Signaling In Crc and Hccmentioning
confidence: 99%
“…[ 78 ] identified Wnt5a (wingless/integrated-5) as a key regulator of pulmonary pericyte/EC interaction and showed that reduced production of Wnt5 by microvascular ECs resulted in decreased migration and polarisation of pericytes towards ECs, resulting in the development of persistent PH in mice. Intriguingly, HIF-2α drove Wnt5a expression in multiple duodenal organoid models [ 79 ], but it is not known if the same mechanism is relevant for the pulmonary microvascular ECs.…”
Section: Hif As a Key Molecular “Hub” In Lung Physiology And Copdmentioning
confidence: 99%